Instituições de formação profissional - história e perspectivas: o projeto da nova institucionalidade da educação profissional brasileira dos anos 1990 - ARAUJO, Ronaldo Marcos de Lima (2014)
This article problematizes the project of the "new intitutionalism of professional education", present on different federal programs during the governments of President Fernando Henrique Cardoso´s Government, which were meant to promote an extensive renovation of the professional education. We focused on the effects of different programs of professional education in the city of Belém, state of Pará, in the period of 1995 and 2003. We could verify that these programs had been guided by references identified with Pragmatism. And by means of observation and interviews, we could also verify that the renewal of professional education had not been accomplished and that the most evident product of the set of actions undertaken had been the reproduction of the ideas that professional education must be subordinated to the immediate interests of the market. We conclude indicating that a new professional education is still to be constructed.